The Religion and Rituals of the Nomads of Pre-Islamic Arabia: A Reconstruction Based on the Safaitic Inscriptions - Al-Jallad, Ahmad (Ancient Languages and Civilizations, 2022)
This book presents a reconstruction of pre-Islamic Arabian religion based on epigraphic and archaeological sources